Effect of Scaffolding Instructional Strategy and Gender on Academic Achievement of Senior Secondary School Islamic Studies Students - Torpev Terver Francis; Baffa Mukhtar; Kabir Sadiq (Universitas Pendidikan Indonesia (UPI), 2023)
The effect of scaffolding instructional technique and gender on academic performance and retention of senior secondary school Islamic Studies students in Katsina State, Nigeria was investigated in this study. The study's goal was to look at the academic performance of male and female Senior Secondary School II (SSSII) Islamic studies students in Katsina State who were exposed to a scaffolding instruction teaching technique and to see how well they retained the information. To provide direction for the investigation, two research questions and two matching hypotheses were raised and formulated. The investigation was carried out using a quasi-experimental research design. A sample of forty students comprising 17 males and 23 females were selected from Family Support Senior Secondary School Daura using intact class. Data was collected using a validated instrument titled: the Islamic Studies Achievement Test (ISAT) with a reliability coefficient of 0.68. The data were analyzed with descriptive statistics such as mean and standard deviation, as well as an independent sample t-test. When male and female students were exposed to the teaching strategy, the results revealed no significant differences in academic achievement. Because scaffolding education is gender friendly, it is advised that Islamic studies teachers adopt and implement it in secondary schools.